MENGATASI RUGI-RUGI EKSTERNAL DALAM PERENCANAAN TRANSMISI KABEL BAWAH LAUT - Redaksi Tim Jurnal (Sekolah Tinggi Teknik PLN, 2016)
To go to JDPT, improving the capability and reliability of the systems associated therewith, both switching system or transmission media becomes very important. One of the transmission medium that supports JDPT is a submarine cable which is better known fiber cable optick. Fiber optic cable is suitable for transmission of digital and analog, has a damping small and wide bandwidth, flexible to increase channel capacity and have a diameter or size is small and the way the installation is also not much different from the usual multipair cable. The use of fiber optics is increasingly widespread, so some efforts to reduce losses arising from the installation of fiber optic cables is still being done to improve the quality of fiber optic transmission.